What determines firms' credit to access in the absence of effective economic institutions: Evidence from China - Tong Fu (Kiel Institute for the World Economy (IfW), 2017)
The existing literature suggests that economic institutions determine the allocation of resources for economic growth. As an important counterexample, although China has one of the world's fastest-growing economies, its legal and financial systems are underdeveloped. With evidence from China, the author confirms that government intervention positively and causally determines firms' access to credit. He further provides evidence that government intervention enables firms' profit through facilitating access to credit. This evidence confirms that the mechanism of government intervention allows firms' access to credit and then enables the firms to obtain relatively large profit. Ultimately, this paper reveals that, in the absence of effective economic institutions, government intervention channels the allocation of capital.
Keywords: O17; G21; G28; C51; 330; access to credit; government intervention; mediation effect